SWOT Analysis of Arrum Hajj Products of Pawnshop Parepare Area - Sunarta, Desy Arum; Mahsyar, Mahsyar (Al-Iftah: Journal of Islamic studies and society, 2020)
This study discusses the service process on Hajj Arrum products, SWOT analysis of Hajj Arrum products and Islamic economic perspective on the SWOT analysis used on Hajj Arrum products. The purpose of empirical data regarding the service process carried out on Hajj arrum products, the use of SWOT analysis and Islamic economic perspectives on Hajj Arrum products Pawnshop Parepare Area. This type of research is an empirical study using descriptive qualitative. Primary data sources in this study are Business Deputy, Sales Asmen and Staff. Whereas secondary data are scientific books, journals, and theses. The results of this study are: (1) The service process of the Hajj arrum product undertaken by Pawnshop Parepare Area to customers is in the form of a gold deposit worth Rp. 1,900,000 by customers. The contract used for hajj arrum products is rahn (2) One of the results of a SWOT analysis conducted by the Pegadaian Board of Directors when looking at the development of hajj arrum products in general. The issuance of Board of Directors Regulation Number 21 of 2019 concerning the Second Amendment to Board of Directors Regulation Number 132/DIR I/2017 concerning Arrum Hajj Pawnshop Standard Operating Procedure as a form of maximizing arrum hajj products in the face of developments in the business world (3) Based on the Islamic economic perspective on arrum hajj products through SWOT analysis in product development that the service process is carried out based on SOP that have been issued and based on the DSN-MUI fatwa in its administration.